2019
DOI: 10.1186/s12883-019-1520-2
|View full text |Cite
|
Sign up to set email alerts
|

The EXPANd trial: effects of exercise and exploring neuroplastic changes in people with Parkinson’s disease: a study protocol for a double-blinded randomized controlled trial

Abstract: BackgroundParkinson’s disease (PD) affects many physiological systems essential for balance control. Recent studies suggest that intensive and cognitively demanding physical exercise programs are capable of inducing plastic brain changes in PD. We have developed a highly challenging balance training (the HiBalance) program that emphasizes critical aspects of balance control through progressively introducing more challenging exercises which incorporates dual-tasking. Earlier studies have shown it to be effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 57 publications
1
43
0
1
Order By: Relevance
“…This study used a cross-sectional design based on baseline data from the EXercise in Parkinson’s disease and Neuroplasticity Trial (EXPANd; registered at clinicaltrials.gov NCT03213873). 17 Data collection commenced in January 2018 and concluded in August 2019. Assessments were performed in a university setting.…”
Section: Methodsmentioning
confidence: 99%
“…This study used a cross-sectional design based on baseline data from the EXercise in Parkinson’s disease and Neuroplasticity Trial (EXPANd; registered at clinicaltrials.gov NCT03213873). 17 Data collection commenced in January 2018 and concluded in August 2019. Assessments were performed in a university setting.…”
Section: Methodsmentioning
confidence: 99%
“…After each block, the participants had six seconds to respond to how many plus signs they had seen by choosing between four alternatives (ranging from 0 to 7 integers from the correct alternative). This non-verbal multiple-choice question was used instead of a free recall to minimize the risk of movement when the task is to be performed in the MRI scanner in our upcoming trial [ 17 ]. The participants were instructed to focus on both tasks to an equal extent.…”
Section: Methodsmentioning
confidence: 99%
“…A large randomized controlled trial (RCT) by our research group showed that a highly challenging balance training positively affected gait and balance as well as the dual task performance of a cognitive task (performed while walking) in individuals with mild to moderate PD [ 15 , 16 ]. We are now planning a similar trial with the addition of brain activity assessments as measured by functional magnetic resonance imaging (fMRI), see our study protocol [ 17 ]. During fMRI, we plan to use a version of the SRTT as a measure of implicit sequence learning ability and to use a similar choice reaction time task with the addition of a simple counting task (from here on referred to as the dual task), as a measure of dual task ability.…”
Section: Introductionmentioning
confidence: 99%
“…A few obstacles include which biological markers are the most useful for measuring neuroplasticity and what imaging techniques/tools would be most helpful to document changes in the neural networks [107]. A clinical trial [108] and a feasibility study [109] for exercise-induced neuroplasticity in PD are currently underway.…”
Section: Role Of Exercise In Neuroplasticitymentioning
confidence: 99%